Legal Uncertainty of Administrative Sanctions in the Implementation of Digital Business: A Case Study of PT Sinergi Millenium Sekuritas - Tiara Aprilia; Suherman, Suherman (Journal of Law, Politic and Humanities, 2024)
This research aims to analyze administrative sanctions in digital business, particularly focusing on investment aspects involving PT Sinergi Millenium Sekuritas. The urgency of this study lies in the rapid development of digital business, which necessitates a graduated and progressive approach to administrative sanctions that can support overall digital business growth.The research adopts a normative legal approach, emphasizing conceptualization and relevant legal provisions. The practical application of administrative sanctions in digital business becomes relevant when examining how the OJK enforces administrative sanctions against PT Sinergi Millenium Sekuritas. In a specific case, OJK imposed an administrative sanction by revoking PT Sinergi Millenium Sekuritas' license due to the company's failure to include Equity Appendices and Agency Appendices in the Repo Agreement.The research findings highlight legal issues related to administrative sanctions in digital business, particularly the uncertainty surrounding their implementation. The key question is whether administrative sanctions should be applied immediately through license revocation or whether a gradual approach, starting from warnings to eventual license revocation, is more appropriate. The implication of administrative sanctions lacking legal certainty is the risk faced by digital business operators who fail to provide mandatory information or data in their digital operations. Consequently, they may face direct administrative sanctions, such as license revocation. However, it is essential to recognize that making license revocation the primary step in administrative sanctions could adversely impact the business climate. Therefore, further consideration is necessary regarding utility, value, and efficiency aspects when implementing administrative sanctions in the digital business context.